(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
Dutch director Sacha Polak’s Dirty God (2019) is the first narrative film with a female lead whose scars are real, and arguably the first to tackle the assumption that scars (especially on a woman’s body) are shameful or tragic. Vicky Knight, who plays Jade, a young woman rebuilding her life after an acid attack, has talked about the revelation of seeing her body on screen after enduring years of abuse because of her appearance. Polak ‘saved my life’ she says, by enabling her to see her scarred body as beautiful, ‘a piece of art.’ Like any art form, film has the potential to be transformative, and in interviews both Knight and Polak have repeatedly spoken of their work in those terms. This article uses Dirty God to think about what is at stake in the dismantling of stereotypes and the reclamation of beauty — a goal shared by many disability rights campaigners. Made at a time when escalating cases of acid violence in London were making headlines around the world, Polak’s film prompts comparisons with Katie Piper’s Beautiful (2011) and other survivor memoirs. Privileging imperfection over repair and fragility over strength, it challenges existing portrayals of disfigurement and, in the process, offers a more radical understanding of beauty and authenticity.